The Effect of Percentage Permeability in Composite Structure of Spur dike with Vane on a Sedimentation Pattern in 180̊ mild curve - sina Cheraghchi; Mahmood Shafai Bajestan (علوم و مهندسی آبیاری, 2023)
One common method for Blank River protection and restoration is use of Spur dikes. Spur dikes either in the forms of group or single, depending on their permeability is classified an permeable and impermeable. Spur dikes restore flow pattern and prevent erosion of river banks. This leads to stability and immovability of river. However, they have some disadvantages; on installation they require drying river and erosion around their structure causes destruction (Anonymous, 2002, 2003) and (Anonymous, 2010). Due to the mentioned disadvantages use of spur dikes will be halted and use of vane, which has a higher environmental compatibility, is suggested. This study aims to introduce “composite structure”; a new structure with a combination of a Spur dike with different permeability and a single vane. The main aim of this study is to increase the amount of sediment transported behind the structure by water flow produced by the vane in the combination structure.